Effect of imagined movement speed on subsequent motor performance - Louis, M.; Guillot, A.; Maton, S.; Doyon, J.; Collet, C. (Journal of Motor Behavior, 2008)
Researchers realize that motor imagery (MI) duration is closely linked to actual motor action duration. In 2 experiments, the authors investigated the effect of changing MI speed on actual movement duration over a 3-week training period. Experiment 1 involved 2 series of body movements that 24 participants mentally performed faster or slower than their actual execution speeds. The fast MI group's actual times decreased on subsequent performance. Participants in Experiment 2 were 21 skilled athletes who increased (decreased) their well-rehearsed actual movement times after MI training at a slow (fast) speed. The effect was taskrelated, however: MI affected only self-initiated movement. The effect of MI on actual speed execution supports the ideomotor theory because anticipation of sensory consequences of actions is mentally represented.